Studying of Optical System Includes Elliptical Aperture Point Spread Function - Hassan, A. B.; Ali, H. M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this work, optical system with elliptical aperture using point spread function was studied. This is due to its comparison with an optical system with a circular aperture. The present work deals with the theoretical study of intensity distribution within the image. In this work, a special formula was derived which is called the point spread function (PSF) by using a pupil function technique. The work deals with the limited optical system diffraction only (ideal system), and the system with focal shift. Also a graphic relation was founded between eccentricity and the best of focal depth given to at least (80%) of intensity.